2017
DOI: 10.1039/c7cp02670f
|View full text |Cite
|
Sign up to set email alerts
|

Porous organic cage membranes for water desalination: a simulation exploration

Abstract: Porous organic cages (POCs) have emerged as a new class of porous materials and received considerable interest for their potential applications. Herein we report the first proof-of-concept simulation study on POC membranes for water desalination. Among the five POC membranes, CC2 is the best for water desalination with performance superior to other membranes reported in the literature. The membrane flexibility is revealed to have a weak effect on water permeation. To provide further microscopic understanding, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…The cation and anion rejections of CC3 and CC19 are predicted to be 100% (Fig. 4b and Supplementary Table 3 ), which is consistent with the above experimental results and the previous simulation studies on the crystalline and amorphous membranes of CC3 19 21 . Despite its large pore windows, CC5 only showed slight to negligible cation permeation, which is consistent with the experimental observation.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The cation and anion rejections of CC3 and CC19 are predicted to be 100% (Fig. 4b and Supplementary Table 3 ), which is consistent with the above experimental results and the previous simulation studies on the crystalline and amorphous membranes of CC3 19 21 . Despite its large pore windows, CC5 only showed slight to negligible cation permeation, which is consistent with the experimental observation.…”
Section: Resultssupporting
confidence: 90%
“…Interestingly, the performance of CC1 provides evidence that the POCs may exist as crystalline structures within the lipid bilayer. CC1, despite exhibiting an apparent lack of porosity when in crystalline state 19 , may contain some interconnected networks when the molecules pack in an amorphous fashion 20 . Therefore, some water permeation may be expected if CC1 packs amorphously.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…14−16 Furthermore, proof-of-concept molecular simulation studies were reported to examine crystalline and amorphous POCs for water desalination. 17,18 Attributed to their excellent selectivity, POCs have been explored as fillers in polymer membranes for separation. Lively and co-workers blended amorphous scrambled POCs (AS-POCs) with methylated-polyethylenimine (m-PEI) for SO 2 adsorption; the ASPOCs and mPEI were found to form homogeneous composites with improved adsorption kinetics compared to pure mPEI.…”
Section: Introductionmentioning
confidence: 99%